St. Mary's Aleppo, Sedgwick County - Copeland, James (Kansas State University, The Chapman Center for Rural Studies, 2015)
This study overviews the German-Catholic hamlet of St. Mary’s Aleppo, a church community located in western Sedgwick County, Garden Plain Township. Maps, photographs and personal accounts are included.
James Copeland, “St. Mary’s Aleppo, Sedgwick County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/149.
Keywords: St. Mary's Aleppo; Sedgwick County; Garden Plain; Ost; Father Manz; Angela Schild